Pengaruh profitabilitas, struktur modal, ukuran perusahaan, likuiditas dan kebijakan dividen terhadap nilai perusahaan - Adevia Ananda Gz; G. Anggana Lisiantara (Politeknik Ganesha Medan, 2022)
The value of the company is the company's performance which can be seen from the stock price formed due to the demand and supply of the capital market which gives speculation of the public's assessment of the company's performance. This study aims to examine profitability, capital structure, firm size, liquidity and dividend policy on firm value in mining sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period.sampling technique in this study was using the purposive sampling method with the criteria for manufacturing companies in the mining sector that published complete financial reports in 2017-2021 and manufacturing companies in the mining sector that had complete data relating to the variables used in this study. The analytical analysis method used is multiple linear regression analysis. The data is processed using SPSS 26. The results of this study state that profitability has a positive effect on firm value. Capital structure has a positive effect on firm value. Firm size has a positive effect on firm value. Liquidity has a positive effect on firm value. Dividend policy has a positive effect on firm value.